Improving Speaking Ability of the Third Semester Students of English Department of FKIP UKI Toraja Through Paraphrasing - Selvy Panggua (LPPM UKI Toraja, 2017)
The objective of this research is to find out whether or not the paraphrasing improves speaking ability of the third semester students of English Department of FKIP UKI Toraja. This research used an experimental design that applied Experimental and control group. The population of this research was the third semester students of English Department of FKIP UKI Toraja, academic year 2012/2013. The number of this population was 320 students which consist of nine classes. Because the number of the population was big in number, so the writers took out 16 students as the sample of this research. The sample took randomly from all classes. The result of data analysis shows that paraphrasing improves speaking skill of the third semester students of English Department of FKIP UKI Toraja. This believe is based on the fact that the mean score of the experimental group was 6.2 and the control group was 5.7. It shows that the mean score of the experimental group is greater than the control group. The different between experimental and control group is 0.5. Based on the result of data analysis, the writers concludes that paraphrasing improves speaking skill of the third semester students of English Department of FKIP UKI Toraja academic year 2012/2013